The relationship between technology acceptance model (TAM) and employees' motivation in using technology / Eza Elhanis Mohd Sayuti - Mohd Sayuti, Eza Elhanis (Faculty of Business and Management, 2018)
This study was conducted to analyze the relationship between technology acceptance model (TAM) and employees' motivation in Ministry of Tourism and Culture (MOTAC). The rapid growth of technology have prompted many difficulties and changes also it bring some beneficial and improve work efficiency. Both results can influence on their motivation. Using a survey method by distributing questionnaires, data were gathered from 80 respondents from MOTAC, Putrajaya. According to Hazlin and Faridah (2010), technology acceptance model was used to determine the relationship between perceived ease of use and perceived usefulness of using technology towards employees' motivation. The result shows that the issues of technology acceptance are positively and significantly correlated with employees' motivation. The study concludes that technological issues investigated were very important in ensuing the relationship between technology acceptance and employees' motivation